Pengaruh Total Utang, Total Modal terhadap Laba Bersih dengan Current Ratio sebagai Variabel Intervening pada Sektor Industri Keuangan Sub Asuransi Umum di Bursa Efek Indonesia Periode 2019-2023 - Saqina, Meidina; Fathiyah, Fathiyah; Masnun, Masnun (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the effect of total debt and total capital on net income with the current ratio as an intervening variable in general insurance subsector companies listed on the Indonesia Stock Exchange for the 2019–2023 period. This study uses a quantitative approach. The sampling technique used purposive sampling, resulting in 8 companies as research samples. The data used are secondary data sourced from the company's financial statements. Data analysis was conducted using path analysis and hypothesis testing through the F test and t test. The results of the study indicate that total debt and total capital simultaneously have a significant effect on the current ratio and net income. Partially, total debt has a negative and significant effect on the current ratio, while total capital has a positive and significant effect on the current ratio. However, total debt and total capital do not have a significant effect on net income. In addition, the current ratio also does not have a significant effect on net income. Net income is proven to play a role as an intervening variable in the relationship between total debt and total capital on the current ratio in general insurance subsector companies listed on the Indonesia Stock Exchange for the 2019–2023 period.